1987
DOI: 10.4315/0362-028x-50.3.239
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Staphylococcal Enterotoxins A, B and C in a Buffered System

Abstract: The heat stability of staphylococcal enterotoxins A, B and C (SEA, SEB, SEC) in phosphate buffered saline solution at a concentration of 100 ng per ml indicated that normal cooking times and temperatures are unlikely to completely inactivate the toxins. The order of heat resistance of the three toxins was SEC>SEB>SEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 0 publications
2
14
0
1
Order By: Relevance
“…SA enterotoxin is not degraded by proteases such as trypsin, renin or papain and is heat stable even at 100C for 180 min or 120C for 20 min (Borja and Bergdoll 1967; Huang et al . 1987; Tibana et al . 1987).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SA enterotoxin is not degraded by proteases such as trypsin, renin or papain and is heat stable even at 100C for 180 min or 120C for 20 min (Borja and Bergdoll 1967; Huang et al . 1987; Tibana et al . 1987).…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 shows the distribution of SA samples according to toxin production and the presence of toxin genes. SA enterotoxin is not degraded by proteases such as trypsin, renin or papain and is heat stable even at 100C for 180 min or 120C for 20 min (Borja and Bergdoll 1967;Huang et al 1987;Tibana et al 1987). Among the 30 SA isolates evaluated here, 19 (63%) produced SEA, while SEA + SEB and toxin specific genes were detected in 16 (53%).…”
Section: Toxigenicity Of the Ec And Sa Isolatesmentioning
confidence: 99%
“…The toxins have molecular weights (MWs) ranging from 27,000 to 34,000, and SEB has an MW of 28,336 with an isoelectric point (pI) of 8.6 (Jones and Khan 1986). The relative thermostability of these toxins is staphylococcal enterotoxin C (SEC) > SEB > SEA (Tibana et al. 1987), and the chemical and physical properties of these toxins are summarized by Jay (2000).…”
Section: Introductionmentioning
confidence: 99%
“…The toxins have molecular weights (MWs) ranging from 27,000 to 34,000, and SEB has an MW of 28,336 with an isoelectric point (pI) of 8.6 (Jones and Khan 1986). The relative thermostability of these toxins is staphylococcal enterotoxin C (SEC) > SEB > SEA (Tibana et al 1987), and the chemical and physical properties of these toxins are summarized by Jay (2000). The minimum level of enterotoxin to cause gastroenteritis in humans was approximately 1 ng/g or ng/mL of food (Noleto and Bergdoll 1982;Jay 2000), while Newsome (1988) and Tatini et al (1984) reported less than 1 m g of toxin ingestion.…”
Section: Introductionmentioning
confidence: 99%
“…The relative thermostability of these toxins are SEC > SEB >SEA (Tibana 1987) and the chemical and physical properties of these toxins are summarized by Jay (2000). The minimum level of enterotoxin to cause gastroenteritis syndrome in humans were approximately 1 ng/g or ng/mL of food (Jay 2000;Noleto and Bergdoll 1982) while Newsome (1988) and Tatini er al.…”
Section: Introductionmentioning
confidence: 99%